Serotype detection, molecular characterization and genetic relationship study on Pasteurella multocide local isolate - Sri Suryatmiati Prihandani; Susan M Noor; Asmarani Kusumawati (Indonesian Center for Animal Research and Development (ICARD), 2017)
Pasteurella multocide is a bacteria that causes snoring disease or Haemorrhagic Septicaemia (HS) in Indonesia with high mortality and morbidity in heterogeneous species including cattle as a source of animal products with high economic value. The complexity of conventional and biochemical identification is a major obstacle in the detection of this disease because P. multocide has five serotypes A, B, D, E and F, while serotype B is the leading cause of HS cases in Asia including Indonesia. Therefore, it is necessary to conduct a research that can determine the serotype and molecular characterization and genetic study of five isolates of P. multocide from Lampung and Kupang by Polymerase Chain Reaction (PCR) technique. After PCR was performed on specific genes, capsular genes, 16S rRNA genes, sequencing and analysis using Bioedit, BLASTn, CLUSTALW and MEGA7.0.25, it was found that the five isolates were divided into two serotype groups: A and B. Isolate P. multocide (code: PMc) from Lampung is high homolog with ATCC isolate 12945, so it can be used as a positive control serotype A in the detection of other P. multocide isolates with PCR. Whereas, isolate P. multocide from Kupang can be used as positive control of serotype B because it is identical to P. multocide PMTB2.1 (CP007205.2) from Malaysia that is isolated from buffalo infected by HS.